1999
DOI: 10.1111/j.1550-7408.1999.tb04612.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Deep Phylogenetic Relationships among Cyanobacteria and Plastids by Small Subunit rRNA Sequence Analysis1

Abstract: Small subunit rRNA sequence data were generated for 27 strains of cyanobacteria and incorporated into a phylogenetic analysis of 1,377 aligned sequence positions from a diverse sampling of 53 cyanobacteria and 10 photosynthetic plastids. Tree inference was carried out using a maximum likelihood method with correction for site-to-site variation in evolutionary rate. Confidence in the inferred phylogenetic relationships was determined by construction of a majority-rule consensus tree based on alternative topolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
774
1
9

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,317 publications
(833 citation statements)
references
References 71 publications
20
774
1
9
Order By: Relevance
“…The first PCR was carried out using 27F (Lane, 1991) and 1401R (Nübel et al, 1996) primers, while for the second PCR, 27F-GC and 519R (Turner et al, 1999) primers were applied (which resulted in 16S rRNA gene amplicons containing the V1-V3 variable regions to get high resolution DGGE patterns; Yu and Morrison, 2004;Youssef et al, 2009) Bacterial community profiles were revealed and compared by DGGE using 7% (w/v) polyacrylamide gel containing a 40 to 60% gradient of denaturants (100% is defined as 40% formamide and 7 M urea). The electrophoresis was carried out at 60 °C in 1× Tris-acetate-EDTA (TAE) buffer at 120 V for 14.5 hours using a phorU-2 electrophoresis system (Ingeny International, Goes, Netherlands).…”
Section: 3denaturing Gradient Gel Electrophoresis (Dgge)mentioning
confidence: 99%
“…The first PCR was carried out using 27F (Lane, 1991) and 1401R (Nübel et al, 1996) primers, while for the second PCR, 27F-GC and 519R (Turner et al, 1999) primers were applied (which resulted in 16S rRNA gene amplicons containing the V1-V3 variable regions to get high resolution DGGE patterns; Yu and Morrison, 2004;Youssef et al, 2009) Bacterial community profiles were revealed and compared by DGGE using 7% (w/v) polyacrylamide gel containing a 40 to 60% gradient of denaturants (100% is defined as 40% formamide and 7 M urea). The electrophoresis was carried out at 60 °C in 1× Tris-acetate-EDTA (TAE) buffer at 120 V for 14.5 hours using a phorU-2 electrophoresis system (Ingeny International, Goes, Netherlands).…”
Section: 3denaturing Gradient Gel Electrophoresis (Dgge)mentioning
confidence: 99%
“…The primers used for this reaction were the bacterial universal primers 16S8F (5'-AGAGTTTGATCCTGGCTCAG-3') [40] and 16S1492R (5'-TACGGYTACCTTGTTACGACTT-3') [41]. The PCR amplifications were performed as described by [42], using 2 µl of reaction mixture obtained combining three parallel replicates.…”
Section: Clone Library Analysismentioning
confidence: 99%
“…The extra aaRS genes in eukaryotes are presumed to be derived from those contained in the original mitochondrial endosymbiont (for a review of mitochondrial origins, see Gray et al 1999) and subsequently transferred to the nucleus, as no known extant mitochondrial genomes encode an aaRS. Plants received a third and more recent influx of aaRS genes with the acquisition of plastids (for reviews of plastid origins, see Douglas 1998;Martin et al 1998;Turner et al 1999). Like mitochondria, plastids have lost most of their original genes, some of which have been transferred to the nucleus.…”
Section: Introductionmentioning
confidence: 99%